Examining the relationship between mindfulness levels and burnout syndrome among family medicine residents - Ayşe Gümüş Özçelik; Zeynep Unus Yılmaz; Egemen Tural; Akın Dayan (Discover Psychology)
Abstract Background Recent studies highlight that mindfulness-based interventions can enhance physicians’ well-being and care quality. Burnout, common in primary care, harms physicians’ health, productivity, and patient care. This study investigates the link between mindfulness and burnout in family medicine residents. Methods This prospective, cross-sectional, descriptive study included residents who had completed their first year and were actively working in the Family Medicine Clinics of a University Hospital. Participants were administered a sociodemographic data form, Mindful Attention Awareness Scale, and the Maslach Burnout Inventory through face-to-face interviews and online surveys. Statistical analyses were performed using IBM SPSS Statistics 21.0, with a significance level set at p < 0.05. Results A total of 191 residents participated in the study, 71.7% of whom were female. The age distribution was as follows: 71.3% were aged 24–30, 27.7% were aged 31–35, and 1% were aged 36–40. A negative correlation was found between mindfulness and both emotional exhaustion and depersonalization, while a positive correlation was observed between mindfulness and personal accomplishment. Emotional exhaustion was identified as a statistically significant negative predictor of mindfulness, whereas personal accomplishment was a positive predictor. Additionally, participants who enjoyed and dedicated time to a hobby demonstrated higher levels of mindfulness. Conclusion Reduced emotional exhaustion and heightened personal accomplishment boost mindfulness. Low mindfulness among physicians is a critical concern, impairing both professional performance and patient care. Enhancing family medicine residents’ work conditions and promoting hobbies could mitigate burnout and improve mindfulness.